Revisiting education and training programs: Geoarchaeology as a driver of interdisciplinary reasoning - Oosterbeek, Luiz; Adewumi, Opeyemi L.; Rosina, Pierluigi; Gomes, Hugo; Cura, Pedro; Garcês, Sara (Frontiers in Earth Science, 2022)
Abstract A core problem of contemporary society finds its roots in the education system and the divides created between humanities and sciences, obliterating integrated reasoning. This problem affects society at large and has a severe impact in the mindset of leadership, precluding in depth debate involving citizens that have a lack of understanding of the basic notions and concepts that drive other agencies. This is why the Lisbon Declaration, approved at the European Humanities Conference upon proposal of UNESCO, CIPSH and FCT, calls for units of humanities and sciences integrated teaching, at all levels of education, including PhD. In this chapter we discuss the potential contribution of geoarchaeology for that aim, considering that it sits at the heart of humanities-sciences interaction, thus allowing for bridging science methods with human behavior at large. Geoarchaeology is one of the most important archaeological research methods that offers unprecedented level of integration between disciplines and geoarchaeological research. It is a good example of how geosciences can contribute to re-think education, in terms of research-based education: learning to research, learning that research on earth and humans is by nature interdisciplinary, learning to design answerable questions, learning to frame scientific analysis within wider meanings and prospects, fostering the understanding of truth and of criteria for truth. On one hand, it is a unique bridge between human and earth sciences and on the other hand, between science and understanding human behavior which have a pivotal role to play in communicating and educating about sustainability. The multidisciplinary dimensions of geoarchaeological approaches have encouraged continuous development and innovation of methods and approaches that have opened new possibilities for explorations in geosciences, research on earth and humans, learning to design answerable questions and fostering the understanding of truth and criteria for truth. Examples run from basic stratigraphy assessments onsite to complex analytics, as in the cases of pigment analysis and micromorphology. The chapter discusses some of the specific experiences of bridging geoarchaeology and education and concludes with some specific suggestions in terms of future experiments.